Efficient coverage algorithm for mobile sensor network with unknown density function. Issue 6 (6th February 2017) - Zuo, Lei; Yan, Weisheng; Yan, Maode
Abstract : This study investigates the coverage control problems for the mobile sensor network in a given domain, in which the density function characterising the distribution of the information of interest is unknown. To approximate the density function, we develop an adaptive spatial estimation algorithm for the mobile sensor network. Then, a distributed coverage control strategy is proposed to drive the sensors to the optimal locations. To further improve the efficiency of the coverage process, the authors apply the consensus mechanism into the spatial estimation algorithm and propose an improved control strategy such that the coverage system can converge to the optimal deployment effectively. The convergences of the proposed coverage systems are proved through Lyapunov stability theorem. Moreover, the authors show that the convergence rate of the consensus‐based spatial estimation algorithm is faster than the distributed case. Finally, numerical simulations are provided to illustrate the proposed approaches.